2020
DOI: 10.1158/0008-5472.can-19-1117
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally Active Androgen Receptor Splice Variants Promote Hepatocellular Carcinoma Progression

Abstract: Owing to the marked sexual dimorphism of hepatocellular carcinoma (HCC), sex hormone receptor signaling has been implicated in numerous aspects of liver cancer pathogenesis. We sought to reconcile the clear contribution of androgen receptor (AR) activity that has been established in preclinical models of HCC with the clinical failure of AR antagonists in patients with advanced HCC by evaluating potential resistance mechanisms to AR-targeted therapy. The AR locus was interrogated for resistance-causing genomic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
3
23
0
1
Order By: Relevance
“…As a transcription factor, AR mainly contains ligand‐independent AF1 and AF2, required for cognate ligand binding. In addition, it has been reported that AR‐V7 is a well described variant in prostate cancer and HCC 11,13 . We thus turned to examine the effect of PRPF6 on the transactivation mediated by AR‐AF1, AR‐AF2, or AR‐V7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a transcription factor, AR mainly contains ligand‐independent AF1 and AF2, required for cognate ligand binding. In addition, it has been reported that AR‐V7 is a well described variant in prostate cancer and HCC 11,13 . We thus turned to examine the effect of PRPF6 on the transactivation mediated by AR‐AF1, AR‐AF2, or AR‐V7.…”
Section: Resultsmentioning
confidence: 99%
“…Androgen receptor, as a member of the nuclear receptor superfamily, is a transcription factor activated by ligand (androgen, DHT) to induce a series of target genes. Growing evidence reveals that AR‐induced target genes transcription is important for the development of HCC progression, although the effect of antiandrogen therapy is not satisfactory in clinical liver cancer 8‐11 . This indicates that the AR signaling pathway and the regulation of the oncogenic AR action would be more complicated in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, our report showed that orchiectomy significantly reduced serum testosterone level and hepatic tumorigenesis of Ras-Tg males [63] and artificially increased serum testosterone levels of Ras-Tg females significantly promoted the hepatotumorigenesis (data not show). Although the overexpression or variant of AR has been considered to play a dominant role in HCC [64][65][66], others showed decreased expression of AR in HCC [57,67,68]. These conflicting results regarding the expression and role of AR in HCCs required more detailed investigations [58].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of AR-SV in liver cancer leads to the progress of liver cancer and the resistance to traditional AR antagonists. The successful therapy targeting AR-SVs is beneficial to liver cancer [ 46 ]. Target prediction and pathway enrichment revealed that 14 bioactive compounds (notoginsenoside R1, ginsenoside Re, ginsenoside Rg1, ginsenoside Rb1, ginsenoside Rd, chenodeoxycholic acid, cholic acid, glycodeoxycholic acid hydrate, deoxycholic acid, taurocholic acid, astragaloside A, ginsenoside Rd, sodium taurodeoxylate, and taurochenodeoxycholic acid) act on pathways in cancer signaling pathway and play a therapeutic role in liver cancer by regulating the expression of AR.…”
Section: Discussionmentioning
confidence: 99%